2020
DOI: 10.1123/ijsnem.2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Hydrogel Products Do Not Improve Performance or Gastrointestinal Distress During Moderate-Intensity Endurance Exercise

Abstract: The benefits of ingesting exogenous carbohydrate (CHO) during prolonged exercise performance are well established. A recent food technology innovation has seen sodium alginate and pectin included in solutions of multiple transportable CHO, to encapsulate them at pH levels found in the stomach. Marketing claims include enhanced gastric emptying and delivery of CHO to the muscle with less gastrointestinal distress, leading to better sports performance. Emerging literature around such claims was identified by sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
0
20
4
Order By: Relevance
“…A recent review highlighted the lack of evidence for benefits from the use of sodium alginate and pectin added to a CHO beverage on physiological or GID symptoms during moderate intensity exercise ( 36 ). Current, mechanism-driven research has shown that a hydrogel can form around a CHO ( 37 ), which occurs in vivo ( 18 ) and subsequently enhances GE ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review highlighted the lack of evidence for benefits from the use of sodium alginate and pectin added to a CHO beverage on physiological or GID symptoms during moderate intensity exercise ( 36 ). Current, mechanism-driven research has shown that a hydrogel can form around a CHO ( 37 ), which occurs in vivo ( 18 ) and subsequently enhances GE ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current, mechanism-driven research has shown that a hydrogel can form around a CHO ( 37 ), which occurs in vivo ( 18 ) and subsequently enhances GE ( 19 ). Following this, however, there have been several studies which showed no differences from “standard” CHO beverages when comparing various physiological markers (e.g., ExCHO, whole-body oxidation rates and blood metabolites) and subjective markers (e.g., RPE and GID symptoms) [as reviewed elsewhere ( 36 )]. The lack of any clear benefit when ingesting CHO with additional sodium alginate and pectin may be due to several factors.…”
Section: Discussionmentioning
confidence: 99%
“…4). More concentrated blends of cleverly formulated drinks, gels, 35 or simple use of easily digestible CHO food sources may be required and should be tested for individual preference and tolerance. In our analysis above, a drink to thirst strategy sometimes resulted in consumption of more, sometimes less, fluid and energy than needed for the circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite only eight of the seventy-six total responses in the study dealing with sessions <45 min, where CHO intake is not required (21) , or mouth-rinse strategies can provide ergogenic benefits during race conditions (22) , especially if fasted (23) . On-bike nutrition can be met through the use of homemade solutions, or commercially available products, including hydrogels, which have anecdotal support to mitigate GI issues (24) . In light of this finding, it is suggested that cyclists consider the role of indoor training to practice and optimise individual CHO intake while heeding nutrition recommendations, with the understanding that selfmade CHO supplementation is a suitable strategy if required (21,25) .…”
Section: Discussionmentioning
confidence: 99%